Bond performance between corroded steel bars and concrete in cathodic protection system with CFRP as anode. (1st April 2023) - Huang, Xiaoxu; Zhou, Yingwu; Zheng, Xubin; Xing, Feng; Sui, Lili; Hu, Biao
Abstract: Impressed current cathodic protection (ICCP) has been proven to be an effective technique to inhibit steel corrosion. Based on the ICCP method, a hybrid reinforced concrete (RC) structural system of carbon fiber reinforced polymer (CFRP) bars/steel bars was proposed, in which CFRP bars are used as the reinforcement material and anode material simultaneously. The bond performance of the steel bar-concrete interface with ICCP was studied here. The effects of the ICCP current density and the pre-corrosion ratio on bond performance were considered through a series of experiments, including the accelerated corrosion test, the ICCP test, the linear polarization test, and the pull-out test. Experimental bond strengths were also compared with values predicted by existing models. The results showed that cathodic protection with the CFRP bar as the anode material was effective, and further steel corrosion was inhibited significantly, leading to an improvement in the corroded steel bar-concrete bond performance. In addition, the bond strength decreased gradually as the ICCP current density and the pre-corrosion ratio increased. A significant discrepancy existed between the experimental bond strength and the predicted value, indicating that the bond performance varied with the paths to achieve the same corrosion state.